NEEDS ANALYSIS ON ENGLISH LANGUAGE LEARNING AMONG PHARMACY DIPLOMA STUDENTS - Atur Semartini (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2022)
English use in tourism sector is different from business or pharmacy field, so English language learning based on needs has to be carried out. To determine the needs for English language learning in certain fields requires a needs analysis whose results can later be applied in the curriculum. This study aims to investigate Â the needs of Pharmacy Diploma students for English language learning. The subjects of this study were 57 Pharmacy Diploma students Â who had also worked as pharmaceutical technicians. The data was obtained by using a questionnaire which was then analysed for its frequency, percentage, mean, and standard deviation. Based on the research, the most important skills for Pharmacy Diploma students were Speaking and Translation. Meanwhile, the most significant functions of English were to read scientific articles, operate tools or computers, and communicate with patients and colleagues. Furthermore, the problems experienced by Pharmacy Diploma students in the use of English were difficulties in understanding someone speaking English quickly and also vocabulary related to the health or pharmacy. It then can be concluded that English language learning needed by Pharmacy Diploma students is related to speaking, translation, and also vocabulary enrichment related to health and pharmacy. Compiling curriculum adjusting the needs and the use of English by students is recommended.